Adjusting Rate of Return and Present Value for Price-Level Changes. - Duvall, Richard M.; Bulloch, James (The Accounting Review, 1965)
Abstract We have given formulas to aid in the computation of real rates of return and present values if price-level changes have occurred or are anticipated, in order to better evaluate the performance of various assets or the feasibility of acquiring an asset. It has been demonstrated that price-level changes can seriously distort the rate of return realized on an investment. Finally, it has been argued that one should consider price-level changes, actual or anticipated, before appraising the performance of an asset or purchasing one.